Correlation Between Previous Caesarean Section and Adverse Maternal Outcomes Accordingly With Robson Classification: Systematic Review and Meta-Analysis - Jamshed, Shazia; Chien, Shuo-Chen; Tanweer, Afifa; Asdary, Rahma-Novita; Hardhantyo, Muhammad; Greenfield, David; Chien, Chia-Hui; Weng, Shuen-Fu; Jian, Wen-Shan; Iqbal, Usman (Frontiers in Medicine, 2022)
Background: The increasing rates of Caesarean section (CS) beyond World Health Organization (WHO) standards (10-15%) pose a significant global health concern. Objective: Systematic review and meta-analysis to identify association between CS history and maternal adverse outcomes for the subsequent pregnancy and delivery among women classified in Robson classification (RC). Search strategy: PubMed/Medline, EbscoHost, ProQuest, Embase, Web of Science, BIOSIS, MEDLINE, and Russian Science Citation Index were searched from 2008 to 2018. Selection criteria: Based upon Robson classification, studies reporting one or more of the 14 adverse maternal outcomes were considered eligible for this review. Data collection: Study design data, interventions used, CS history, and adverse maternal outcomes were extracted. Main results: From 4,084 studies, 28 (n = 1,524,695 women) met the inclusion criteria. RC group 5 showed the highest proportion among deliveries followed by RC10, RC7 and RC8 (67.71%, 32.27%, 0.02%, 0.001%). Among adverse maternal outcomes, hysterectomy had highest association after preterm delivery OR=3.39 (95% CI 1.56-7.36), followed by Severe Maternal Outcomes OR=2.95 (95% CI 1.00-8.67). We identified over one and a half million pregnant women, of whom the majority were found to belong to RC group 5. Conclusions: Previous CS was observed associated with adverse maternal outcomes for the subsequent pregnancies. CS rates need to be monitored given the prospective risks which may occur for maternal and child health in subsequent births.